Mafalda: Middle Class, Everyday Life, and Politics in Argentina, 1964-1973 - Cosse Larghero, Isabella (2014)
In this article I reconstruct the history of Mafalda, the famous comic strip by the Argentine cartoonist Quino that was read, discussed, and viewed as an emblematic representation of Argentina’s middle class. With the aim of contributing to discussions on the interpretation of the middle class in Argentina and Latin America, I examine the emergence, circulation, and sociopolitical significance of the comic from its first strips in 1964 until Quino stopped producing new installments in 1973, making use of two conceptual and methodological approaches: a perspective situated at the intersection of the everyday and the political, as well as a consideration of humor as a way of exploring social identities. I argue first that Mafalda’s ironic and conceptual humor worked with the contradictions of the middle class as it faced social modernization, cultural and political radicalization, and a weakening democracy. Second, I suggest that the strip contributed to a representation of a heterogeneous middle class marked by ideological differences but nonetheless conceived as one. Third, I claim that such a representation lost its relevance with the political polarization and violence of the 1970s, as portraying a middle class—or a society—united despite differences was no longer feasible in that context. To illustrate this, the article closes by noting that, shortly after Mafalda was discontinued, state terrorism would brutally demonstrate just how little space there was in Argentina for the young, antiestablishment generation depicted in the strip.